Planned Change Strategies at a Business Company - Ruiz Chávez, Ramón (Universidad de Sonora, 2020)
It is very common to find small family-owned businesses experiencing operational difficulties between their organization and the accomplishment of their objectives. In a great number of cases, these family-owned businesses are founded to fulfill some circumstantial situation, whether by the necessity of generating income to support its members, or by the continuity of operating the conditions of an inherited family-owned business. This work presents the intervention process accomplished to small familiar business dedicated to the wholesale and retail of fruits, vegetables and groceries following FariaMello’s model adjusted, in order to improve its performance through a soft change to the organization by means of implementation of several strategies applied making the best utilization of available resources.